Contraceptive practices and associated social covariates: an experience from two districts of West Bengal, India - Haldar, A; Baur, B; Das, P; Misra, R; Pal, Ranabir; Roy, R P (Nepal Journal of Epidemiology, 2012)
Background Contraceptive practice acceptable to Indian society is said to be associated with socio-economic status, education, practice of the area and other factors. Population stabilization and a gradual lowering of population growth is the basic aim behind contraceptive practice. Objectives The study was conducted to assess current status of contraceptive practice and social covariates (age, type of family, religion, socio-economy, education, etc). Materials and Methods A community based cross-sectional study was conducted among four thousand eligible couples in Howrah and Paschim Midnapore districts of state of West Bengal, India from March to September 2009. By stratified multistage random sampling technique, 32 areas were selected from two districts; villages of sub-centre zone and wards of municipality; from each selected area; 125 eligible couples were interviewed by house to house survey. Results The contraceptive acceptance (prevalence) rate (CAR) by any method was 65.3 percent and couple protection rate (CPR) by approved methods was 58.4 percent in these two districts of West Bengal. In Paschim Midnapore district CAR was higher (67.4%) than Howrah district (63.3%). Similarly in Howrah district CPR was less (54.3%) than Paschim Midnapore district (62.6%). Type of family, age and literacy status of female partners, religion and social class were associated with adoption of family planning methods by the eligible couples with inter-district variation. Conclusion Area specific multipronged tailor-made interventions are needed through Behaviour Change Communication (BCC) for promotion of acceptance of both the temporary & permanent methods of contraception at the appropriate time to achieve small family norm.